A statistical model of the rate-dependent fracture behavior of dental polymer-based biomaterials - Schrader, Peer; Schmidt, Alexander; Schlenz, Maximiliane A.; Kolling, Stefan; Wöstmann, Bernd; Berlinger, Marcel; Justus Liebig University Giessen (My University, 2023)
An insight into the fracture behavior of dental polymer-based biomaterials is important to reduce safety hazards for patients. The crack-driven fracture process of polymers is largely stochastic and often dependent on the loading rate. Therefore, in this study, a statistical model was developed based on three-point bending tests on dental polymethyl methacrylate at different loading rates. The fracture strains were investigated (two-parameter Weibull distribution (2PW)) and the rate-dependency of the 2PW parameters were examined (Cramér-von Mises test (CvM)), arriving at the conclusion that there could be a limiting distribution for both quasi-static and dynamic failure. Based on these findings, a phenomenological model based on exponential functions was developed, which would further facilitate the determination of the failure probability of the material at a certain strain with a given strain rate. The model can be integrated into finite element solvers to consider the stochastic fracture behavior in simulations.
Keywords: Biocompatible materials; Weibull statistics; Dental materials; Fracture strain; Statistical models; ddc:610